Populismo en América Latina: desde la teoría hacia el análisis político : Discurso, sujeto e inclusión en el caso Argentino - Retamozo, Martín (2014)
The current processes have reignited the debate surrounding populism in Latin America; however, the category's theoretical status is far from being clarified. In this context, the article suggests that populism could contribute to political theory, starting from the open perspective of Ernesto Laclau, while also drawing on the definition of functional fields in its political analysis: populism as discourse; as a construction of a political subject; and as promoting the inclusion of all that has been excluded in the social order. Starting from these developments, the second part of the article uses these contributions to analyze the current political process in Argentina, and specifically the phenomenon of kirchnerism.